Artérias das glândulas tireóides em avestruzes (Struthio camelus) - Honorato, Angelita das Graças de Oliveira (2011)
We studied the arteries leading to the thyroid glands, addressing their number, origin and organization in 30 ostriches (Struthio camelus) with up to 30 days of age in both sexes. The birds were injected with Neoprene latex 450 colored and fixed in aqueous 10% formaldehyde. The thyroid glands were presented as an organ pair, pale reddish brown, oval-shaped ends, some being elongated in the craniocaudal direction and flattened dorsoventrally. Located on the edge of the cranial cavity celomatic, manteined syntopy with the vagus nerve, jugular vein and common carotid artery. The thyroid glands were collateral arteries: common carotid, ascending esophageal, tracheal ascending, subclavian, and common esophageal tracheal vagus nerve. The number of vessels ranged from one to five, and were called thyroid, cranial artery, middle cranial, middle, middle caudal and caudal at both antimeres. The vessels were present in the side right in 28 (93,3%) cases as cranial thyroid, nine (30%) as middle cranial, 12 (40%) as middle, nine (30%) as middle caudal and 28 (93,3%) as caudal. And on the left side in 27 (90%) cases as cranial thyroid, six as middle cranial, 12 (40%) as middle, six (20%) as middle caudal and 27 (90%) as caudal. The thyroid artery was observed in two (6,6%) cases in side right and three (10%) on the left side.